Strengthening Creative Character of Students in Cumo Pulai Art Studio - Badral, Lailai; Alam, Masnur; Candra, Hadi (Institut Agama Islam Negeri Kerinci, Indonesia, 2024)
This study explores the contribution of extracurricular art activities in strengthening students’ creative character through the Cumo Pulai Art Studio at SMAN 4 Sungai Penuh, Jambi, Indonesia. Character education is a central mission of national education, emphasizing not only academic excellence but also moral, social, and creative capacities needed in the 21st century. Creativity, defined as originality, flexibility, elaboration, and problem-solving ability, is an essential competence; however, preliminary observations indicated that students in the art studio often lacked initiative, showed low motivation, and produced limited original works. This study aimed to examine the processes of strengthening creative character, the outcomes achieved, and the factors that support or hinder the implementation of the program. Employing a qualitative descriptive design, data were collected through observations, semi-structured interviews with students, teachers, and studio coaches, and document analysis. Participants were selected purposively from students actively engaged in the art studio. Data were analysed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings show that the Cumo Pulai Art Studio created a conducive learning environment where students enhanced originality through choreography and music composition, improved collaboration through group performance, and developed discipline and responsibility by following structured rehearsals. The program also fostered cultural preservation by encouraging students to value and reinterpret local traditions in creative ways. Despite these benefits, challenges such as limited facilities, lack of skilled instructors, and inconsistent student attendance were identified. The study concludes that extracurricular art education can significantly strengthen creative character and cultural appreciation, suggesting that integrating such programs into schools offers an effective strategy for holistic student development.